2009
DOI: 10.1002/ca.20786
|View full text |Cite
|
Sign up to set email alerts
|

Distal biceps brachii tendon anatomy revisited from a surgical perspective

Abstract: The distal biceps brachii tendon is commonly susceptible to traumatic injury. This study aimed to describe the morphology of the distal biceps brachii tendon in relation to the commonly used endobutton repair of tendon rupture. The results suggested that the distal tendon is a series of distinct bands of variable number. These bands are obscured surgically by the tendon sheath. Upon opening this sheath, blunt dissection of the tendon released fibrous connections between the tendon bands. Adjacent bands were va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…While 1 study showed a definable separation of tendon fascicles from each muscle belly in 10 of 15 specimens. 1 Another study showed much variability in tendon fascicle separation and noted that complex interdigitations of multiple tendon fascicles were often present 16 (Fig. 3).…”
Section: Anatomymentioning
confidence: 99%
“…While 1 study showed a definable separation of tendon fascicles from each muscle belly in 10 of 15 specimens. 1 Another study showed much variability in tendon fascicle separation and noted that complex interdigitations of multiple tendon fascicles were often present 16 (Fig. 3).…”
Section: Anatomymentioning
confidence: 99%
“…3,27 More recently, several anatomic studies have brought forth the awareness that the distal biceps tendon may actually remain as 2 distinct anatomic and functional tendon bundles with varying amounts of interconnections. 1,6,8,9 In light of these findings, some researchers have speculated that each musculotendinous unit of the biceps could have separate roles in elbow and forearm motion. 6,8,19 Eames et al hypothesized that the short head musculotendinous unit is positioned to be a better flexor, while that of the long head a better supinator.…”
mentioning
confidence: 99%
“…In most of the reported cases, it inserts into either the tendon or the aponeurosis of biceps brachii. Insertion into both may cause clinical entrapment syndrome [18,19]. In the present study also, in 2 out of three cases, it was inserted into the tendon.…”
Section: Resultsmentioning
confidence: 54%